Clinico-dermatoscopic and histopathological evaluation of a case of generalized lichen nitidus - Sunanda Arun Mahajan; Surender Singh; Yallappa Ramachandrappa Kabbannavar; Vidya D Kharkar (Wolters Kluwer Medknow Publications, 2022)
Lichen nitidus (LN) is a rare asymptomatic skin disease composed of numerous tiny, shiny, flat papules mainly over the chest, forehead, neck, forearm, and glans penis. They are of two types based on distribution, localized which is more common compared to generalized. Dermoscopy helps in differentiating LN from other similar dermatoses such as lichen planus, keratosis pilaris, follicular eczema, lichen spinulosus, which is non-invasive. We describe a 15-year-old female with generalized lichen nitidus with palms, soles, and nail involvement with dermoscopic features and histopathological correlation.